A multi-center prospective cohort study of benign breast disease and risk of subsequent breast cancer - Kabat, Geoffrey C. (2010)
OBJECTIVE: We used a nested case–control design within a large, multi-center cohort of women who underwent a biopsy for benign breast disease (BBD) to assess the association of broad histologic groupings and specific histologic entities with risk of breast cancer. METHODS: Cases were all women who had a biopsy for BBD and who subsequently developed breast cancer; controls were individually matched to cases and were women with a biopsy for BBD who did not develop breast cancer in the same follow-up interval as that for the cases. After exclusions, 1,239 records (615 cases and 624 controls) were available for analysis. We used conditional logistic regression to estimate odds ratios and 95% confidence intervals (CIs). RESULTS: Relative to non-proliferative BBD/normal pathology, the multivariable-adjusted odds ratio for proliferative lesions without atypia was 1.45 (95% CI 1.10–1.90), and that for atypical hyperplasia was 5.27 (95% CI 2.29–12.15). The presence of multiple foci of columnar cell hyperplasia and of complex fibroadenoma without atypia was associated with a non-significantly increased risk of breast cancer, whereas sclerosing adenosis, radial scar, and papilloma showed no association with risk. CONCLUSION: Our results indicate that, compared to women with normal pathology/non-proliferative disease, women with proliferative disease without atypia have a modestly increased risk of breast cancer, whereas women with atypical hyperplasia have a substantially increased risk.